2001
DOI: 10.1046/j.1365-2893.2001.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotypes: distribution and clinical significance in patients with cirrhosis type C seen at tertiary referral centres in Europe

Abstract: The aim of this study was to evaluate the distribution and clinical significance of hepatitis C virus (HCV) genotypes in European patients with compensated cirrhosis due to hepatitis C (Child class A) seen at tertiary referral centres. HCV genotypes were determined by genotype-specific primer PCR in 255 stored serum samples obtained from cirrhotics followed for a median period of 7 years. Inclusion criteria were biopsy-proven cirrhosis, absence of complications of cirrhosis and exclusion of all other potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…The percentages of sequenced and classified genotypes are listed in Table I and are in perfect agreement with those reported in different studies [Saracco et al, 2000;Fattovich et al, 2001;Haushofer et al, 2001]. By direct sequencing, we were unable to type all 29 samples that were totally ascribed to specimens with a viral load of <70,000 HCV IU, as determined by quantitative HCM-2 assay.…”
Section: Resultssupporting
confidence: 87%
“…The percentages of sequenced and classified genotypes are listed in Table I and are in perfect agreement with those reported in different studies [Saracco et al, 2000;Fattovich et al, 2001;Haushofer et al, 2001]. By direct sequencing, we were unable to type all 29 samples that were totally ascribed to specimens with a viral load of <70,000 HCV IU, as determined by quantitative HCM-2 assay.…”
Section: Resultssupporting
confidence: 87%
“…[33] In this study, SVR24 rate was higher in subtype 1b patients than in subtype 1a patients and subtype 1b was identified as a predictor of treatment success; this is consistent with previous studies [12,34,35] and is of clinical importance considering the high prevalence of genotype 1b Europe. [36] The power of HCV subtype in predicting response to TVR has been attributed to the higher genetic barrier of subtype 1b to the development of resistance mutations compared with subtype 1a. [37] This is due to the fact that subtype 1a virions require a single nucleotide mutation in the position 155 to resist TVR, in comparison with subtype 1b virions which require the mutation of two nucleotides in the same position to develop TVR resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Only six studies recruited some patients after 2000 and may therefore have followed the EASL Guidelines; the corresponding pooled RR (95% CI) was slightly higher than that based on the other 51 papers (2.30 (1.08-4.93) vs. 1.62 (1.41-1.87), meta-regression p-value: 0.36). Among the 21 studies providing age-adjusted RRs, only three [11,13,53] included only histologically diagnosed patients, while 14 included a mixture of patients diagnosed on the basis of imaging (angiography, ultrasonography, CT) or tumor markers such as a-fetoprotein, with [5,10,12,33,49,[54][55][56][57][58][59][60] or without [32,61] histological criteria; in other three studies HCC was histologically or cytologically confirmed, [1,62,63] and one study [64] did not provide information on HCC diagnosis. Anyway, if a misclassification of HCC patients has occurred, it was likely to be independent of HCV genotype status; this undifferential misclassification could at least underestimate the RR, and could not be the reason of the significant positive association observed here.…”
Section: Summary Estimatementioning
confidence: 99%